Intestinal Surgery Contributes to Acute Cerebellar Ataxia Through Gut Brain Axis - Yu, Jie; Fan, Yuanming; Wang, Li; Huang, Yanjuan; Xia, Jingyi; Ding, Le; Wu, Chun-Feng; Lu, Xiaopeng; Ma, Gaoxiang; Kim, Samuel; Zheng, Guo; Guo, Hu; et al. (Frontiers in Neurology, 2019)
Introduction Acute cerebellar ataxia (ACA) is the most common form of pediatric ataxia. Changes in gut flora can modulate the nervous system, influencing brain function via the gut-brain axis (GBA). This study aimed to illustrate the relationship between intestinal microbiota and ACA. Method A total of 30 and 12 children were randomly sampled from history of intestinal surgery (HOIS) and no intestinal surgery groups (NHOIS), respectively. In addition, 10 healthy children who sought physical examination in Children’s Hospital of Nanjing Medical University were recruited as a control group. The stool samples were 16S rRNA detected. Results We observed that many ACA children had intestinal surgery history prior to the onset of ACA. The 16S rRNA sequencing indicated that HOIS and control groups were well distinguished by principal component analysis. The discrepancy between HOIS and NHOIS groups were also displayed by principal component analysis score plot. However, no differences were found between NHOIS and control groups. The results of student’s t test were consistent with principal component analysis. A total of 9 different genera were identified between HOIS and control groups. Five genera and a phylum showed significant differences between HOIS and NHOIS groups. Conclusion Altered genera and phyla associated with ACA were identified. Our findings provide new insight into treating and preventing ACA.